Pewilayahan Komoditas Pertanian Berdasarkan Zona Agroekologi (AEZ) Skala 1:50.000 Kabupaten Muaro Jambi dan Kota Jambi Provinsi Jambi . Based Agricultural Commodities of Agroecology Zone Map Scale 1: 50.000 at Muaro Jambi and Jambi District, Jambi Province - Hendri, Jon; Purnama, Hendri; Buyung Saidi, Busyra (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Hendri J, Purnama H, Saidi BB. 2019. Based agricultural commodities of agroecology zone map scale 1: 50.000 at Muaro Jambi and Jambi District, Jambi Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 277-286. Palembang: Unsri Press. Support regional development plans Jambi province, especially Muaro Jambi and Jambi City regency, has done the preparation of maps of land resources and agricultural commodities zoning map scale of 1: 50,000 which can be used as the basis for planning the development of agriculture. Research methodology includes several stages of the preparation, the field research and data collection. The results showed that Agroclimate Zone Muaro Jambi and Jambi City belong to the agro-climatic zones B1, Consists of 21 land units where 8 land units are behind river meanders marsh, swamp behind the tidal plains and peat plivio marin, whereas 13 land units consist of tectonic flat to undulating plains with the parent material of clay. Based on the agro-ecological zone is divided into regions, namely the development of 1). Zone IV/ Wr / Wrh an area of 82.516 ha for paddy rice and maize, 2) Zone IV/DFH/Defh an area of 124.510 ha to dryland agriculture crops and horticulture, 3). Zone III/Defh an area of 78.095 ha to the development of dryland agriculture with annual crops based food crops, 4) Zone II/Deh an area of 16.519 ha to dryland agriculture with annual crops/plantation. 5) Zone V/Wh (forest wetlands) for agricultural or limited natural forest area of 277.263 ha. The application technology of land management for the development of agricultural commodities on the topography flat with the level of soil fertility Low devoted to the development of food crops annuals with soil fertility improvement, While on lands with undulating topography to hilly preferred for annual crop development coupled with land conservation technology in the form of alley cropping and terrace.Keyword: agroecology zone, agricultural development, Muaro Jambi